2001
DOI: 10.1021/ja0033739
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Active Catalyst in Late Transition Metal-Mediated Ring-Opening Polymerization (ROP) Reactions:  Mechanistic Studies of the Platinum-Catalyzed ROP of Silicon-Bridged [1]Ferrocenophanes

Abstract: Current mechanisms for the transition metal-catalyzed ring-opening polymerization (ROP) of [1]-ferrocenophanes and related strained species such as cyclic carbosilanes invoke a homogeneous mechanism. In this paper we describe experiments which indicate that the Pt(0)-catalyzed ROP of silicon-bridged [1]-ferrocenophanes proceeds mainly by a heterogeneous mechanism with colloidal platinum as the catalyst. Mechanistic studies were initiated to elucidate the fate of the ferrocenylsilane component of the precatalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 32 publications
1
89
1
4
Order By: Relevance
“…36 In the case of Pt, it has been reported that heterogeneous metal colloids form as the active catalysts, and postulated that oxidative-addition and reductive-elimination reactions at the metal surface resulted in formation of the polymer. 37 For silicon-bridged ferrocenophanes in which one Cp ring is methylated, Pt II -catalysed ROP proceeds solely by selective cleavage of the Si-Cp H (Cp H = C5H4)bond to yield a regioregular, crystalline PFS, unlike thermal ROP which affords a regioirregular amorphous material. 38 Transition metal-catalysed ROP is advantageous in that it does not require high monomer and solvent purity unlike anionic ROP (Section 2.2.4.1), or the high temperatures used in thermal ROP.…”
Section: Catalytic Ropmentioning
confidence: 99%
See 3 more Smart Citations
“…36 In the case of Pt, it has been reported that heterogeneous metal colloids form as the active catalysts, and postulated that oxidative-addition and reductive-elimination reactions at the metal surface resulted in formation of the polymer. 37 For silicon-bridged ferrocenophanes in which one Cp ring is methylated, Pt II -catalysed ROP proceeds solely by selective cleavage of the Si-Cp H (Cp H = C5H4)bond to yield a regioregular, crystalline PFS, unlike thermal ROP which affords a regioirregular amorphous material. 38 Transition metal-catalysed ROP is advantageous in that it does not require high monomer and solvent purity unlike anionic ROP (Section 2.2.4.1), or the high temperatures used in thermal ROP.…”
Section: Catalytic Ropmentioning
confidence: 99%
“…The mechanism is believed to involve competition between the Si-H and strained Si-C bonds for oxidative-addition at the metal centre. 37,40 Use of such materials with Si-H groups has allowed the preparation of regioregular, comb-shaped graft copolymers, star-shaped polymers, and block copolymer architectures. 38 Chlorosilanes such as ClMePhSiH are more effective terminating agents than Et3SiH due to steric considerations, and also introduce a Si-Cl end functionality on telechelic polyferrocenylsilanes.…”
Section: Catalytic Ropmentioning
confidence: 99%
See 2 more Smart Citations
“…21 42,43 Recent detailed mechanistic work has indicated that the major catalyst in the Pt-promoted ROP reactions is colloidal metal. 44 Transition-metal-catalyzed ROP is a mild method that does not require monomer with an exceptional degree of purity and has now been developed to the stage at which considerable control over polymetallocene architectures is possible. 45 For example, [1]silaferrocenophanes with different cyclopentadienyl rings can undergo regioregular transition-metal-catalyzed ROP, whereas thermal ROP affords a regioirregular PFS material.…”
Section: (Y ϭ H) With Controlled Molecular Weights and Narrow Moleculmentioning
confidence: 99%